L'élaboration d'un curriculum de français pour les chefs de mission sud-africains - Burger, Marali (French Language and Literature, 2017)
This study aims to develop a French curriculum that is responsive to the specific needs of South African Heads of Mission. Firstly, the context highlights the role of Heads of Mission in the implementation of South Africa's foreign policy against the backdrop of the history of diplomacy and South Africa's international relations under the auspices of the Department of International Relations and Cooperation (DIRCO). Taking into account South Africa's representation in a total of 31 French-speaking countries, the importance of having knowledge of the French language is highlighted. The subsequent theoretical framework outlines issues related to the teaching of French (including teaching French as a Foreign Language – TFFL), the notion of French for Specific Purposes (FSP), as well as the methodology that inform the practical aspect of this project. The final section presents the results of the needs analysis, the data collection, and the development of teaching material from the collected data. These steps culminate in the development of a curriculum that addresses the needs of South African Heads of Mission. Two lesson plans and an evaluation activity based on the curriculum are also suggested.